Ceramic-based upconversion phosphors - Giri N.K.; Agnihotri N.; Prakash R. (My University, 2025)
The optical transitions of lanthanides responsible for upconversion are susceptible to their local environment. Hence, spectral conversion properties can be tailored for specific photonic applications by choosing the host material of explicit nature. Ceramic materials, supposed to be most versatile branch of materials comprise of inorganic (synthetic or natural), non-metallic, polycrystalline materials formed by the combination of metallic and non-metallic elements. Properties of such materials depend on type of bonding between the constituent atoms and the way atoms are packed together. Based on raw materials used for synthesis of ceramics they can be categorized as traditional or advanced ceramics. Lanthanide activated ceramic phosphors are termed as advanced ceramics as they use high purity starting raw materials mostly obtained by synthetic routes. Typically, lanthanides doped low phonon energy ceramic materials show strong upconversion due to reduction in non-radiative losses. While, glass-ceramics which is another class of ceramic materials combines the excellent properties of glass and phosphor. They retain decent transparency, high acceptance of lanthanide doping, mechanical and chemical stability of glasses with brilliant upconversion properties of phosphor and most suited for advanced photonic applications.This chapter presents an overview of properties of lanthanide doped ceramic based upconversion phosphors. The synthesis strategies, followed by basic and advanced characterization techniques of ceramic phosphors are briefly conferred. It sums up the exciting properties of up-converting ceramic phosphor materials which makes them an excellent choice for light emitting devices, energy harvesting technologies and bioimaging applications. © 2022 Elsevier Inc. All rights reserved.